Experiential Learning Through Impact Projects: A Framework for Implementation - Thian, Lok Boon; Ng, Veronica; Chang, Yen Heng (Journal of University Teaching and Learning Practice, 2026)
While the literature has recognised the benefits of experiential learning in the field, there still exists a lack of a pragmatic implementation framework to ensure its effective implementation. This paper reports on the design and development of an experiential learning practical implementation project in a university. Using design-based research, the framework was developed and improved through two cycles of implementation over one year, involving academics and students from nine science and social science disciplines. Central to the framework are Impact Projects that leverage the three design elements of authenticity, structure, and agency. Data were drawn from academic (qualitative) interviews and reflections, supplemented by a student survey; these were analysed to develop the implementation framework. Based on staff insights, a three-stage framework was developed consisting of a) Conceptualisation of Impact Projects, b) Integration of Impact Projects into Curriculum, and c) Implementation of Impact Projects. Findings highlight the challenges faced during implementation and the strategies to tackle those challenges. The proposed framework highlights the importance of proper conceptualisation of the Impact Projects involving the partners, beneficiaries and academics to ensure alignment. The framework has expanded knowledge of implementing experiential learning in the field by offering more detailed, practical steps to ensure it achieves the intended learning outcomes.